A common LPA null allele associates with lower lipoprotein(a) levels and coronary artery disease risk - Kyriakou, T; Seedorf, U; Goel, A; Hopewell, J; Clarke, R; Watkins, H; Farrall, M (Lippincott Williams and Wilkins, 2014)
OBJECTIVE - Increased levels of lipoprotein(a) are a highly heritable risk factor for coronary artery disease (CAD). The genetic determinants of lipoprotein(a) levels are mainly because of genetic variation in the apolipoprotein(a) gene (LPA). We have tested the association of a relatively common null allele of LPA with lipoprotein(a) levels and CAD risk in a large case-control cohort. We have also examined how null allele genotyping complements apolipoprotein(a) isoform typing to refine the relationship between LPA isoform size and circulating lipoprotein(a) levels. APPROACH AND RESULTS - The LPA null allele (rs41272114) was genotyped in the PROCARDIS (Precocious Coronary Artery Disease) case-control cohort (4073 CAD cases and 4225 controls). Lipoprotein(a) levels were measured in 909 CAD cases and 922 controls; apolipoprotein(a) isoform size was estimated using sodium dodecyl sulfate-agarose gel electrophoresis and a high-throughput quantitative polymerase chain reaction-based method. Null carriers are common (null allele frequency, 3%) and have significantly lower circulating lipoprotein(a) levels (P=2.1×10) and reduced CAD risk (odds ratio, 0.79 [0.66-0.97]; P=0.023) compared with noncarriers. An additive allelic model of apolipoprotein(a) isoform size, refined by null allele genotype and quantitative polymerase chain reaction values, showed a sigmoid relationship with lipoprotein(a) levels, with baseline levels for longer isoform alleles and progressively higher levels of lipoprotein(a) for shorter isoform alleles. CONCLUSIONS - The LPA null allele (rs41272114) is associated with decreased circulating lipoprotein(a) levels and decreased CAD risk. Incorporating rs41272114 refined apolipoprotein(a) isoform size typing obtained by immunoblotting and quantitative polymerase chain reaction. A joint genomic and isoform analysis revealed details of the relationship between apolipoprotein(a) isoform size and circulating lipoprotein(a) level consistent with a threshold effect on lipoprotein secretion. © 2014 American Heart Association, Inc.